Financial Organization and Operations of the IMF. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1998)
The financial structure and operations of the IMF are described in this pamphlet, as well as the sources of IMF financing, the policies associated with the use of IMF resources, and the role of the IMF as trustee to various accounts that are administered by it.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet